PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2009-2013) - Simanungkalit, Paskah; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2015)
The purpose of this study is to investigate the effect of intellectual capital toward the firm value using the financial performance as intervening variable in manufacturing firms registered in Indonesia Stock Exchange in period 2009-2013. This research examine the relation of three major components of firm’s resources which is capital emloyeed (VACA), human capital (VAHU), and structural capital (STVA) toward the firm value of the company’s financial performance. The firm value is measured using price to book value (PBV) otherwise the company’s financial performance is measured using return on asset (ROA).The samples used ini this study are 25 manufacturing firms in Indonesia Stock Exhange in period 2009-2013. Path analysis used to be analysis technique using program SPSS 20 for windows to determine the effect of mediation.The result of this study show that VACA and VAHU have positively and significant influence on ROA. VACA and ROA have positively and significant influenced and PBV. Financial performance may mediate the relation between VACA and STVA toward firm value.